Technology Transfer Modalities Utilized by Agricultural Extension Workers in Organic Agriculture in Philippines - Mary Yole Apple Declaro-Ruedas (Journal of Agricultural Extension, 2019)
This study determined the profile of agricultural extension workers in the municipalities of San Jose, Magsaysay, Rizal, and Calintaan (SAMARICA), Occidental Mindoro; their technology transfer modalities utilized in extending organic agriculture; problems encountered in the technology transfer; and the relationship between the profile of the agricultural extension workers and the technology transfer modalities utilized in organic agriculture. The respondents of the study were the 42 front line agricultural extension workers in the Local Government Unit. They were selected using simple random sampling. Mean and the Pearson Moment Correlation were used in data analysis. Result shows the agricultural extension workers in SAMARICA Area, Occidental Mindoro have an average age of 48.76 years, with long extension experience of 18.14 years, and had earned a college degree related to agriculture. They â€œalwaysâ€ introduce new technologies and practices on organic agriculture with the farmers through individual farm/ home visits, farmersâ€™ groups meetings, and use of Information and Communication Technologies (ICT)). The agriculture extension delivery system in SAMARICA Area, Occidental Mindoro is facing challenges in implementing organic agriculture initiatives in the municipal level. Furthermore, agriculture extension workersâ€™ age is significantly related to the technology transfer modalities utilized in organic agriculture